Synthesis, antimicrobial, and antiproliferative activities of substituted phenylfuranylnicotinamidines - Youssef MM; Arafa RK; Ismail MA (Dove Medical Press, 2016)
Magdy M Youssef,1,2 Reem K Arafa,3,4 Mohamed A Ismail1,21Department of Chemistry, College of Science, King Faisal University, Hofuf, Saudi Arabia; 2Department of Chemistry, Faculty of Science, Mansoura University, Mansoura, 3Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Cairo University, Cairo, 4Biomedical Sciences Program, University of Science and Technology, Zewail City of Science and Technology, Cairo, EgyptAbstract: This research work deals with the design and synthesis of a series of substituted phenylfuranylnicotinamidines 4a–i. Facile preparation of the target compounds was achieved by Suzuki coupling-based synthesis of the nitrile precursors 3a–i, followed by their conversion to the corresponding nicotinamidines 4a–i utilizing LiN(TMS)2. The antimicrobial activities of the newly synthesized nicotinamidine derivatives were evaluated against the Gram-negative bacterial strains Escherichia coli and Pseudomonas aeruginosa as well as the Gram-positive bacterial strains Staphylococcus aureus and Bacillus megaterium. The minimum inhibitory concentration values of nicotinamidines against all tested microorganisms were in the range of 10–20 µM. In specific, compounds 4a and 4b showed excellent minimum inhibitory concentration values of 10 µM against Staphylococcus aureus bacterial strain and were similar to ampicillin as an antibacterial reference. On the other hand, selected nicotinamidine derivatives were biologically screened for their cytotoxic activities against a panel of 60 cell lines representing nine types of human cancer at a single high dose at National Cancer Institute, Bethesda, MD, USA. Nicotinamidines showing promising activities were further assessed in a five-dose screening assay to determine their compound concentration causing 50% growth inhibition of tested cell (GI50), compound concentration causing 100% growth inhibition of tested cell (TGI), and compound concentration causing 50% lethality of tested cell (LC50) values. Structure-activity relationship studies demonstrated that the activity of members of this series can be modulated from cytostatic to cytotoxic based on the substitution pattern/nature on the terminal phenyl ring. The most active compound was found to be 4e displaying a submicromolar GI50 value of 0.83 µM, with TGI and LC50 values of 2.51 and 100 µM, respectively. Finally, the possible underlying mechanism of action of this series of compounds was investigated by determining their nuclease-like DNA degradation ability in addition to their antioxidant power and all monocations proved to be effective in all assays.Keywords: substituted phenylfuranylnicotinamidines, Suzuki coupling, antiproliferative, antibacterial, antioxidant